Recent developments in studies concerning the multimorbidity of many chronic conditions in elderly individuals with hypertension - Qiaolifanayi Nuermaimaiti; Luo Qin (Guoji laonian yixue zazhi)
Currently, almost 50% of elderly individuals globally experience hypertension. Furthermore, elderly individuals with hypertension frequently experience the presence of many chronic illnesses, known as multimorbidity. This condition adds complexity to the treatment of hypertension, significantly affects the elderly’s quality of life, and places a substantial load on the healthcare system both in terms of medical care and financial resources. This review presents a comprehensive analysis of the epidemiological features of multimorbidity in elderly patients with hypertension. It discusses the difficulties they encounter and the existing options for prevention and management. Additionally, it offers insights into potential areas for future research.